Residential mobility predicts COVID-19 and seasonal flu vaccination behaviors in the United States - Zhang, Ning; Jiang, Tao; Zhang, Ying; Zhao, Gang (Frontiers in Public Health, 2023)
Aims: Vaccination is one of the most effective strategies to contain the transmission of infectious diseases, however, people’s intentions and behavior for vaccination vary across different regions and countries around the world. It is not clear how socioecological factors such as residential mobility influence people’s vaccination behaviors for infectious diseases. Methods: We analyzed public data on residential mobility and vaccination rates for COVID-19 and seasonal flu in the United States and explored how residential mobility in the previous year influence vaccination rates for COVID-19 and seasonal flu (2011-2018) across 50 states of U.S. The data were accessed and analyzed in 2021. Results: Study 1 demonstrated that collective level residential mobility predicted COVID-19 vaccination rates across the United States (B = -168.162, 95% CI [-307.097, -29.227], Adjusted R2 = 0.091, p = .019). Study 2 corroborated this finding by documenting that collective level residential mobility predicted vaccination rates for seasonal flu from 2011 to 2018 across the United States (B = -.789, 95% CI = [-1.018, -.56], Adjusted R2 = 0.222, p < .001). The link between residential mobility and vaccination behavior was robust after controlling relevant variables, including collectivism, cultural tightness-looseness, and sociodemographic variables. Conclusions: Our research demonstrated that residential mobility is an important socioecological factor that influence people’s vaccination behaviors. The results enrich our understanding on the socioecological factors that influence vaccination behaviors and have implications for developing tailored interventions to promote vaccination during pandemics of infectious diseases.